(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Introduction: Medical management of an unruptured ectopic pregnancy with intramuscular methotrexate is a common and cost-effective alternative to surgery1. This therapeutic transition from surgical emergency to medical management has been attributed to early diagnosis through the use of sensitive assays for ?-hCG and the high definition vaginal ultrasound. Objectives: The aim of the study was to observe the efficacy and safety of medical treatment either by a single or multiple dose of methotrexate to cure ectopic pregnancy. Materials and methods: A retrospective study from January 2005 June 2008 was carried out, collecting clinical imaging data and serum ?-hCG, time taken for complete ?-hCG resolution was recorded and negative ?-hCG result was used as an endpoint of successful outcome. Out of 14 cases, where Methotrexate (50 mg I/M) was used, two required surgery for symptom of rupture. In the remaining 12 cases, there was no side effects, complete ?-hCG resolution was achieved in 10 of the12 medically treated cases (85% success rate) within 28 days. Rest of the 2 cases needed multiple doses of Methotrexate. Results: Over all success rate was 85%. In 71% cases recovery was uneventful and complete within 7 days of treatment (Table 1). Two patients needed surgical treatment and in another one case there was abdominal pain which subsided after analgesic. Ten patients were cured by single dose only and 2 patients needed multiple dose. There was no side effects or complication of drug in any case. Conclusion: Methotrexate is safe and effective for unruptured ectopic pregnancies that satisfy the strict criteria with no side effects and the advantage of avoiding invasive surgery. This small trial gave a good impression about medical treatment in selective cases. Bangladesh J Obstet Gynaecol, 2013; Vol. 28(1) : 5-8